Exploring the role of green government publicity influencing people’s pro-environmental behaviors - Lin, Yi; Li, Jiechun; Xiang, Ling (Frontiers in Psychology, 2022)
In recent years government publicity was extensively used to convey environmental issues; therefore, it is important to explore the role of green government publicity influencing people's pro-environmental behaviors. This study is to explore the influence of China’s green government publicity on people’s willingness to use green packaging. This research collected data from Guangzhou of China, we used convenient sampling and online questionnaire survey to gather data, and there were 584 effective samples. Using the statistical software Amos17.0, the results show that green government publicity has a significant positive impact on environmental concerns and moral obligation. Environmental concerns and moral obligation both have positive effects on pro-environmental behaviors. In addition, Environmental concerns and moral obligation all have mediating effects in the relationship between green government publicity and people's pro-environmental behaviors.